Pengaruh Komunikasi, Motivasi Finansial serta Kerjasama Tim terhadap Kinerja Karyawan Pada PT. Eka Print Cabang Monang Maning (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this research is to determine the influence of communication, financial motivation and teamwork on employee performance at PT. Eka Print Monang Maning Branch using a population and sample of 36 employees as research respondents. The sampling technique used in this research is sampling (census), data collection techniques are carried out through observation, questionnaires and documentation. The data analysis technique used in this research is multiple linear regression analysis which is processed using SPSS softwareversion 25. Based on the results of the analysis, this research shows that communication has a positive and significant effect on the performance of PT employees. Eka Print Monang Maning Branch, this means that the better employee communication, the employee performance will increase, Financial motivation has a positive and significant effect on the performance of PT employees. Eka Print Monang Maning Branch, this means that the better the motivation given by the food company leadership, the better the employee performance and teamwork will have a positive and significant effect on employee performance at PT. Eka Print Monang Maning Branch.